Upaya Kemandirian Bahan Baku Obat Dalam Pengembangan Industri Farmasi Di Indonesia - Kartika, Adinda Niki (Berkala Ilmiah Mahasiswa Farmasi Indonesia, 2023)
Domestic pharmaceutical industry is capable of procuring around 75% of drug needs for Indonesian market. However, 90% of raw materials for medicines in Indonesia are still imported. This shows that structure of pharmaceutical industry is not yet optimal and limited to formulation, so it is necessary to optimize research and innovation activities, especially development of pharmaceutical raw materials. Collaboration between government/institutions, pharmaceutical industry, and researchers/academicians is needed in realizing the independence of pharmaceutical raw materials. The policy measure of Presidential Instruction Number 6 of 2016 concerning the Acceleration of the Development of the Pharmaceutical and Medical Devices Industry aims to accelerate the development and self-sufficiency of domestic BBO production. Innovation to build domestic BBO industry is carried out by considering Rencana Induk Pembangunan Industri Nasional (RIPIN) 2015-2035. Based on BPOM RI data for 2022, there are 13 or around 5.8% of industries that produce pharmaceutical raw materials from all pharmaceutical industries in Indonesia. The government has made policies and programs to support development of pharmaceutical industry in the self-sufficiency of pharmaceutical raw materials. Policies that have been issued by the government, namely in the form of: 1) Fiscal incentives 2) TKDN 3) Kawasan Industri Terpadu (KIT) 4) Supervision by BPOM. The growth trend for drug and BBO needs in 2035 will increase by 7% per year and is expected to reach IDR 248 trillion for drug needs and IDR 79 trillion for BBO. This shows that the independence of pharmaceutical raw materials needs to be optimized in the development of the pharmaceutical industry in Indonesia. Keywords: Pharmaceutical Raw Materials, BBO, Innovation, Pharmaceutical Industry